2016
DOI: 10.1007/s11060-016-2156-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial evaluating the effects and intra-tumoral penetration of bortezomib in patients with recurrent malignant gliomas

Abstract: One resistance mechanism in malignant gliomas (MG) involves nuclear factor-κB (NF-κB) activation. Bortezomib prevents proteasomal degradation of NF-κB inhibitor α (NFKBIA), an endogenous regulator of NF-κB signaling, thereby limiting the effects of NF-κB on tumor survival and resistance. A presurgical phase II trial of bortezomib in recurrent MG was performed to determine drug concentration in tumor tissue and effects on NFKBIA. Patients were enrolled after signing an IRB approved informed consent. Treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…This finding is in line with new studies describing unique molecular mechanisms employed by stem cells or their malignant counterparts to maintain their unique functional properties (Dolma et al, 2016;van Galen et al, 2014;Tang and Rando, 2014). Our findings therefore provide a molecular basis for triggering proteotoxic crisis (Urra et al, 2017), either by inhibiting stress response pathways or by increasing ER stress over homeostatic levels, such as by inhibition of proteasome activity (Raizer et al, 2016), as a consideration for GBM treatment.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is in line with new studies describing unique molecular mechanisms employed by stem cells or their malignant counterparts to maintain their unique functional properties (Dolma et al, 2016;van Galen et al, 2014;Tang and Rando, 2014). Our findings therefore provide a molecular basis for triggering proteotoxic crisis (Urra et al, 2017), either by inhibiting stress response pathways or by increasing ER stress over homeostatic levels, such as by inhibition of proteasome activity (Raizer et al, 2016), as a consideration for GBM treatment.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with previous trials using concurrent schedules 22 with intensive and prolonged treatment, as well as with various drug combinations. [33][34][35][36][37][38][39] Our patients scored relatively high on the quality of life EQ-5D-5L questionnaire that was previously validated for the Norwegian population. 40 The ability to perform usual daily activity, ataxia, and changes in strength were the strongest predictors of KPS and this finding is corroborated by a previous study of Norwegian patients after surgery.…”
Section: Discussionmentioning
confidence: 86%
“…However, the promise of bortezomib in vitro has yet to be reflected in clinical trials, with two phase II trials combining bortezomib with tamoxifen[ 43 ] and verinostat[ 44 ] proving ineffectual. A recent phase II study has also demonstrated that combination bortezomib and TMZ was ineffective in rGBM despite promising pre-clinical data[ 45 ]. Measurable concentrations of bortezomib were however found in the tumor tissue post-treatment, strengthening our view that ABC-transporter substrates can penetrate the BBB in GBM.…”
Section: Discussionmentioning
confidence: 99%